Effect on mechanical and microbiological properties of adding calcium glycerophosphate and xylitol to glass ionomer cement - de Azevedo Santana, Juliana; de Lima Navarro, Maria Fidela; Gomes, Leonardo Fernandes; Brighenti, Fernanda Lourenção [UNESP]; de Oliveira, Analú Barros [UNESP]; Fernandes, Gabriela Leal Peres [UNESP]; Nunes, Gabriel Pereira [UNESP]; Danelon, Marcelle (Wiley, 2025)
This study aimed to evaluate the effect on the mechanical and microbiological properties of incorporating calcium glycerophosphate (CaGP) and/or xylitol into resin modified glass ionomer cement (RMGIC). Six experimental cements were tested: i) RMGIC without additions; and RMGIC with ii) 5% xylitol; iii) 10% xylitol; iv) 3% CaGP; v) 3% CaGP and 5% xylitol, or vi) 3% CaGP and 10% xylitol. The compressive strength, diametral tensile strength and surface hardness were determined (24 h and 7 days). Antimicrobial/antibiofilm activity was evaluated. Compressive strength values after 24 h for +3% CaGP & 5% xylitol were higher and similar to RMGIC. After 7 days, +3% CaGP & 5% xylitol presented the highest compressive strength values. The +3% CaGP & 10% xylitol showed the lowest values of diametral tensile strength values (24 h). The RMGIC with +3% CaGP & 5% xylitol showed the highest diametral tensile strength (7 days). The surface hardness (24 h) were highest for the RMGIC and +10% xylitol. After 7 days, +3% CaGP & 5% xylitol showed the highest value. The +3% CaGP & 5% xylitol or +3% CaGP & 10% xylitol showed the lowest levels of microbial/biofilm formation. The addition of CaGP/xylitol promoted improved the mechanical and antibacterial properties of RMGIC.
Keywords: bacterial adhesion; biofilm; performance; phosphates; polyol